Motorcycle Parking Building Planning Based on Green Building Concept for Urban Environment - Novianto, FX Hevie Dwi; Taufikkurrahman, Taufikkurrahman; Wahono, Arif (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The rapid growth of motorcycle ownership in urban areas of East Java has increased the demand for efficient vertical parking facilities; however, most conventional parking structures remain energy-intensive, poorly ventilated, and insufficiently aligned with sustainable civil engineering principles. This study aims to analyze the implementation of green building concepts in the planning of motorcycle parking structures and to evaluate their influence on spatial efficiency, natural ventilation performance, and building energy consumption intensity. The research employs a descriptive-quantitative method with a case study approach focusing on a multi-story motorcycle parking facility in an urban area of East Java. Data were collected through field observations, technical building documentation, structured interviews with two facility managers, and questionnaires administered to 30 parking users. The analysis included calculations of parking space unit requirements, the ratio of ventilation openings to floor area, cross-ventilation performance assessment, and measurement of Energy Consumption Intensity (ECI), which were then evaluated against green building indicators. The results indicate that optimizing natural openings and passive daylighting significantly reduces dependence on mechanical systems, improves users’ thermal comfort, and enhances overall energy efficiency compared to conventional parking models.